Sosialisasi Informasi Dan Edukasi Tentang Dampak Kasus Bulying Terhadap Perkembangan Psikologi Sosial Anak Di Madrasah Tsanawiyah Negeri (MTsN) 2 Kabupaten Bireuen - Agustina Agustina; Rahmad Rahmad; Adri Patria; Nova Nova; Muammar Qadafi; Sabarna Sabarna; Nurjannah Nurjannah; Sunayama Sanna Surya (LPPM Umuslim, 2023)
Based on data from the Aceh Social Service there were 32 cases of violence in 2016, and this continues to increase starting from the elementary, middle and high school levels in Aceh, including cases of violence at Islamic boarding schools in the city of Banda Aceh. Dissemination of Information and Education about the impact of bullying cases on the development of social psychology of children at MTsN Negeri 2 Bireuen Regency which is carried out with dedication, to find out what is meant by bullying and the types of actions included in it, to find out the factors that cause bullying and the impact it has As a result, students' understanding of the dangers of bullying has a negative impact on the development of social psychology of children, giving students an understanding of the importance of helping each other and caring for each other, getting students to respect and respect each other so that students know how to deal with bullying. Equipping Class 3A students with knowledge about bullying and being able to avoid bullying practices at MTsN 2 Bireuen District. The Program Socialization Stage by conducting sociali-zation to the target group and agreeing on the time of implementation of the activities. The program implementation stage at MTsN 2 Bireuen, socializing the activity program to class 3A students and continuing to transfer knowledge and skills from the team to the target group.